Anti-inflammatory Effects of Curcumin in Microglial Cells - Yu, Yangyang; Shen, Qian; Lai, Yihong; Park, Sun Y.; Ou, Xingmei; Lin, Dongxu; Jin, Meiling; Zhang, Weizhen (Frontiers in Pharmacology, 2018)
Lipoteichoic acid (LTA) induces neuroinflammatory molecules, contributing to the pathogenesis of neurodegenerative diseases. Therefore, suppression of neuroinflammatory molecules could be developed as a therapeutic method. Although previous data supports an immune-modulating effect of curcumin, the underlying signalling pathways are largely unidentified. Here, we investigated curcumin’s anti-neuroinflammatory properties in LTA-stimulated BV-2 microglial cells. Inflammatory cytokine tumour necrosis factor-alpha (TNF-alpha, prostaglandin E2 (PGE2), and Nitric Oxide (NO) secretion in LTA-induced microglial cells were inhibited by curcumin. Curcumin also inhibited LTA-induced inducible nitric oxide synthases (iNOS) and cyclooxygenase-2 (COX-2) expression. Subsequently, our mechanistic studies revealed that curcumin inhibited LTA induced phosphorylation of mitogen-activated protein kinase (MAPK) including ERK, p38, Akt and translocation of NF-kappaB. Furthermore, curcumin induced hemeoxygenase (HO)-1HO-1 and nuclear factor erythroid 2-related factor 2 (Nrf-2) expression in microglial cells. Inhibition of HO-1 reversed the inhibition effect of HO-1 on inflammatory mediators release in LTA-stimulated microglial cells. Taken together, our results suggest that curcumin could be a potential therapeutic agent for the treatment of neurodegenerative disorders via suppressing neuroinflammatory responses.